Pengaruh Penggunaan Teknologi Gadget Dalam Pembentukan Kedisiplinan Siswa Ekstrakurikuler Tapak Suci di MAN Palopo - Sulpa Sulpa; Rasyidah Jalil; Rachmat Hidayat (Jurnal Porkes, 2026)
This study was motivated by the phenomenon of increasingly widespread gadget use among students, but there is still a lack of research on its use as a means of character building, particularly discipline in extracurricular martial arts activities. The purpose of this study was to determine the effect of gadget technology use on the character building of discipline among Tapak Suci extracurricular students at MAN Palopo. This study used a quantitative method with a correlation approach. The research population consisted of all Tapak Suci Muhammadiyah extracurricular students at MAN Palopo, with a sample of 20 students selected using purposive sampling based on specific criteria. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis used Pearson's correlation test, simple linear regression, t-test, and F-test with the help of SPSS. The results showed that there was a strong and significant relationship between the use of technological gadgets and student discipline (r = 0.629; p < 0.05). The regression test results showed that the use of gadget technology had a positive and significant effect on the formation of students' disciplinary character with a contribution of 39.6%. This means that the more often students access Tapak Suci educational content through gadgets, the more their disciplinary character and responsibility as students will increase.